All kinds of books - Canizares, Susan; Chessen, Betsey Betsey Franco Chessen; Scholastic Inc. (New York Scholastic, 1999)
Explores the diverse purposes of books, demonstrating how they can be used for activities such as fixing a bike, finding a friend's phone number, or engaging in imaginative play.
Includes full-colour photographs illustrating various types of books and their uses.
Ages 4-8
Keywords: Books and reading